Variables influencing the efficiency and interpretation of reverse transcription quantitative PCR (RT-qPCR): An empirical study using Bacteriophage MS2 - Miranda, Jaclyn A.; Steward, Grieg F. (Journal of virological methods, 2017)
•Increasing total RNA and primer concentrations improved RT efficiency.•At high concentrations, random hexamers performed as well as gene-specific primers.•RNA standards corrected for residual systematic variability in RT efficiency.•Length of the RNA standard dramatically influenced quantification accuracy. Reverse transcription, quantitative PCR (RT-qPCR) is a sensitive method for quantification of specific RNA targets, but the first step of the assay, reverse transcription, is notoriously variable and sensitive to reaction conditions. In this study, we used purified Bacteriophage MS2 genomic RNA as a model virus target to test two different RT enzymes (SuperScript II and SuperScript III), two RT-priming strategies (gene-specific primers and random hexamers), and varying background RNA concentrations (0–50ngμl−1) to determine how these variables influence the efficiency of reverse transcription over a range of target concentrations (101–107 copies μl−1). The efficiency of the RT reaction was greatly improved by increasing both background RNA and primer concentrations, but the benefit provided by background RNA was source dependent. At a given target concentration, similar RT efficiencies were achieved with gene-specific primers and random hexamers, but the latter required much higher concentrations. With random hexamers, we observed a systematic variation in RT reaction efficiency as a function of target concentration. Using an RNA standard curve that was also subject to RT effectively normalized for this systematic variability, but the assay accuracy depended critically on the length of the standard RNA extending to the 3' end of the qPCR target site. Our results shed some light on previous contradictory conclusions in the literature, and provide insights that may aid in the design of RT-qPCR assays and the design of synthetic RNA standards when full-length material is not available.